2021
DOI: 10.3390/ijms22115620
|View full text |Cite
|
Sign up to set email alerts
|

The pLysRS-Ap4A Pathway in Mast Cells Regulates the Switch from Host Defense to a Pathological State

Abstract: The innate and adaptive immune systems play an essential role in host defense against pathogens. Various signal transduction pathways monitor and balance the immune system since an imbalance may promote pathological states such as allergy, inflammation, and cancer. Mast cells have a central role in the regulation of the innate/adaptive immune system and are involved in the pathogenesis of many inflammatory and allergic diseases by releasing inflammatory mediators such as histamines, proteases, chemotactic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This has been true for fungi, yeast, plants, Drosophila , and human cells. Quite strikingly, it was found that the pLysRS–AP4A pathway has profound implications in mast cell activation, reprogramming the cell from host defense to further enhance allergic diseases and cancer metastasis (Yannay-Cohen et al 2009 , Marriott et al 2015 , Yu et al 2019 , Govindaraj et al 2021 ). Similarly, the LysRS-dependent production of AP4A can inhibit the activation of the stimulator of interferon genes (STING) pathway and attenuate inflammatory responses (Guerra et al 2020 ).…”
Section: Ap4a Beyond the Bacterial Kingdommentioning
confidence: 99%
“…This has been true for fungi, yeast, plants, Drosophila , and human cells. Quite strikingly, it was found that the pLysRS–AP4A pathway has profound implications in mast cell activation, reprogramming the cell from host defense to further enhance allergic diseases and cancer metastasis (Yannay-Cohen et al 2009 , Marriott et al 2015 , Yu et al 2019 , Govindaraj et al 2021 ). Similarly, the LysRS-dependent production of AP4A can inhibit the activation of the stimulator of interferon genes (STING) pathway and attenuate inflammatory responses (Guerra et al 2020 ).…”
Section: Ap4a Beyond the Bacterial Kingdommentioning
confidence: 99%
“…However, hybrid presence has also been confirmed inside the mitochondria [ 3 , 4 ], extracellular vesicles (EVs) [ 5 ] and cytosol [ 6 , 7 ]. While mitochondrial hybrids share many behaviours with their nuclear counterpart [ 3 , 4 , 8 ], cytosolic hybrids have an established pro-inflammatory role as activators of the cGAS-STING pathway that triggers the expression of inflammatory genes that can lead to cellular senescence or to the activation of defence mechanisms through the exportation of molecular messages in the tumour microenvironment [ 5 , 8 ]. We have recently identified hybrids also as cargoes for EVs released by 10 Gy-irradiated A549 TP53+ cells, conveying a senescence message able to reach distant sites and mediate abscopal effect [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…MITF is directly involved in histamine and PGD2 production. The Lysyl–tRNA–MITF pathway and its relevance for MC activity were first discovered by Razin et al In this Special Issue, Govindaraj [ 9 ] from Razin’s group reviews the pLysRS–Ap 4 A signaling pathway, providing an additional important step toward a full understanding of the intracellular mechanisms involved in MC activation and beyond. In this context, to further fathom the MC signals that may promote adverse effects, in this Special Issue, Quan et al [ 10 ] review the latest data about the hot and emerging topic of MRGPRX2 receptor.…”
mentioning
confidence: 99%